An Investor's Perspective on Mutual Funding - Dr. G. Velmurugan; Dr. R. Subashini; Dr. N. Saravanabhavan; Mr. Manikandan. S (International Journal on Economics, Finance and Sustainable Development, 2022)
The mutual fund industry has grown rapidly over the previous two decades. The number of plans increases as mobilisation increases. A considerable number of money has been used to help the underprivileged in recent years. In India, the mutual fund industry is critical in meeting the demands of a huge number of regular investors. Mutual funds must meet specific requirements in order to be successful. Mutual fund performance and how it compares to other funds Mutual funds aid regular individuals in identifying investment opportunities and making investment decisions. This study looks at the performance of mutual funds. The fundamental goal of the study is to find out how investors feel about mutual funds. A thorough examination of the existing literature was carried out.